2013
DOI: 10.1021/ar4000289
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Enzymology of Membrane Proteins by Solid-State NMR

Abstract: Membrane proteins catalyze reactions at the cell membrane and facilitate thetransport of molecules or signals across the membrane. Recently researchers have made great progress in understanding the structural biology of membrane proteins, mainly based on X-ray crystallography. In addition, the application of complementary spectroscopic techniques has allowed researchers to develop a functional understanding of these proteins. Solid-state NMR has become an indispensable tool for the structure-function analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 66 publications
(137 reference statements)
0
26
0
1
Order By: Relevance
“…Membrane proteins are also extremely appealing targets for SSNMR since the growth of single crystals for X-ray diffraction experiments is challenging [4][5][6][63][64][65]. SSNMR can access these systems in microcrystalline form as well as in their native lipid environment.…”
Section: Resolution Of Membrane Proteinsmentioning
confidence: 99%
“…Membrane proteins are also extremely appealing targets for SSNMR since the growth of single crystals for X-ray diffraction experiments is challenging [4][5][6][63][64][65]. SSNMR can access these systems in microcrystalline form as well as in their native lipid environment.…”
Section: Resolution Of Membrane Proteinsmentioning
confidence: 99%
“…We therefore do not discuss the use of NMR to study nucleic acid dynamics (Kimsey et al 2015) and structure (Keane et al 2015), or quantitative analysis of protein dynamics using solid state NMR spectroscopy (Lewandowski, 2013;Ullrich & Glaubitz, 2013). We also do not cover the use of NMR to study protein folding or intrinsically disordered proteins Wright & Dyson, 2015), although it is important to note that both fields are relevant to protein function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous electron paramagnetic resonance experiments showed that they rotate upon activation in a counterclockwise direction, thereby opening the conduction pathway (15,16). Furthermore, solid-state NMR (ssNMR), which can be applied in lipid bilayers (17)(18)(19)(20), provided detailed insights into the structural basis of the coupling of KcsA activation and inactivation gates during channel gating (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%